2019
DOI: 10.3389/fcvm.2019.00161
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Technologies for Percutaneous Mitral Valve Repair

Abstract: Mitral regurgitation (MR) is a common disease affecting more than 4 million people in the United States and the European Union. A significant number of percutaneous valves have been developed recently, specifically designed for the mitral anatomy, and with a promising evidence of good procedural and echocardiographic outcomes. However, even if transcatheter mitral valve replacement (TMVR) will have a role in the future of percutaneous treatment of both functional and degenerative mitral regurgitation, percutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In one study examining outcomes of 203 patients with severe MR who have been excluded from the available TMVR protocols, more than 88% of patients were rejected from the early feasibility studies of TMVR due to advanced frailty, with mortality reaching up to 12% in those who were ineligible. That same study found that frailty (15%), severe tricuspid regurgitation (TR) (14%), prior aortic valve therapy (13), mitral anatomical exclusion (16%), severe MAC (7%), and risk of left ventricular outflow tract (LVOT) obstruction (LVOTO; 4%) are the most common causes of TMVR exclusion (6). This review offers a brief insight on the current challenges, potential complications of TMVR, and the measures available to mitigate these complications.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In one study examining outcomes of 203 patients with severe MR who have been excluded from the available TMVR protocols, more than 88% of patients were rejected from the early feasibility studies of TMVR due to advanced frailty, with mortality reaching up to 12% in those who were ineligible. That same study found that frailty (15%), severe tricuspid regurgitation (TR) (14%), prior aortic valve therapy (13), mitral anatomical exclusion (16%), severe MAC (7%), and risk of left ventricular outflow tract (LVOT) obstruction (LVOTO; 4%) are the most common causes of TMVR exclusion (6). This review offers a brief insight on the current challenges, potential complications of TMVR, and the measures available to mitigate these complications.…”
Section: Introductionmentioning
confidence: 89%
“…One advantage of surgical MV intervention is that it can be tailored to target the specific pathology of the valvular apparatus. However, today with the detailed pre-procedural planning and with the availability of several transcatheter devices, a targeted pathology approach could be achieved with transcatheter interventions (13). Moreover, the saddle asymmetrical shape of the nonstiff mitral valve annulus and its anatomical relation to the insertion of the papillary muscles make the task to design a transcatheter heart valve (THV) for the treatment of MR Abbreviations: MR, mitral regurgitation; MV, mitral valve; MVr, mitral valve repair; TMVR, transcatheter mitral valve replacement; TAVR, transcatheter aortic valve replacement; TA, transapical; TF, transfemoral; LV, left ventricle; MAC, mitral annulus calcification; ViV, valve-in-valve; ViR, valve-in-ring; ViMAC, valvein-MAC; MDCT, multidetector cardiac tomography; STS, Society of Thoracic Surgeons; THV, transcatheter heart valve; PVL, paravalvular leak; ASA, alcohol septal ablation; LCx, left circumflex coronary artery; AML, anterior mitral leaflet; LVOT, left ventricular outflow tract; LVOTO, left ventricular outflow tract obstruction; iASD, iatrogenic atrial septal defect.…”
Section: Challenges In Designing a Transcatheter Heart Valve For The Mitral Positionmentioning
confidence: 99%
“…Conversely, mechanical valves are believed to be more resilient as multiple studies report a much lower mortality rate, despite the need for anticoagulation therapy. 31,53,54 The same studies, however, highlighted the worryingly high rates of complications and postoperative mortality. Systematic reviews place the mortality rate anywhere between 10 to 60% after one year, while the risk of developing heart failure can be as high as 31%.…”
Section: Transcatheter Mitral Valve Replacementmentioning
confidence: 96%
“…This is usually the case for older patients with multiple co-morbidities. 7,[27][28][29][30][31] The MitraClip device has 2 essential components: the clip delivery system and a guide catheter. 30 It enters the circulation through the femoral vein and is directed towards the heart.…”
Section: Percutaneous Mitral Valve Repairmentioning
confidence: 99%
See 1 more Smart Citation